2023
DOI: 10.1021/acs.est.2c07976
|View full text |Cite
|
Sign up to set email alerts
|

First Discovery of Iodinated Polyfluoroalkyl Acids by Nontarget Mass-Spectrometric Analysis and Iodine-Specific Screening Algorithm

Abstract: Per-and polyfluoroalkyl acids (PFAAs) including polyfluoroalkyl carboxylic acids and polyfluoroalkyl sulfonic acids are a large category of crucial environmental pollutants of global concern. Besides known PFAAs, numerous unknown species may exist in the environment, urgently needing discovery and characterization. This study implemented nontarget analysis for a group of novel PFAA pollutants, viz., iodinated PFAAs (I-PFAAs) in wastewater from a fluorochemical manufacturing park by liquid chromatography−high-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…The relatively high concentrations together with the calculated ecotoxicities and environmental behaviors demonstrate the high significance of IPFAAs for further investigation. IPFAAs may be unintentional byproducts in production of PFASs, as telechelic fluorinated diiodides, PFIs, and FTIs are reactants commonly used in telomerization processes for industrial synthesis of PFASs. , IPFAAs may also be hydrolysis products of iodinated alkyl acyl fluorides and alkyl sulfonyl fluorides, which are intermediates in synthesis of PFASs. , In addition, the presence of IPFAAs may be in connection with iodine transfer polymerization/copolymerization of vinylidene fluoride in synthesis of polyvinylidene fluoride (a very important fluoropolymer) and copolymers, in which iodofluoroalkanes are often used as chain transfer agents and polyvinylidene fluoride products (oligomers) with an iodo end are generated. , The cascade PIE strategy and data-screening algorithm can be expanded to nontarget identification for other pollutants besides IPFAAs, provided that they can generate diagnostic fragment ions in DDA mode. The nontarget identification and comprehensive characterization outcomes present new insights into the occurrence of IPFAAs in the water environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relatively high concentrations together with the calculated ecotoxicities and environmental behaviors demonstrate the high significance of IPFAAs for further investigation. IPFAAs may be unintentional byproducts in production of PFASs, as telechelic fluorinated diiodides, PFIs, and FTIs are reactants commonly used in telomerization processes for industrial synthesis of PFASs. , IPFAAs may also be hydrolysis products of iodinated alkyl acyl fluorides and alkyl sulfonyl fluorides, which are intermediates in synthesis of PFASs. , In addition, the presence of IPFAAs may be in connection with iodine transfer polymerization/copolymerization of vinylidene fluoride in synthesis of polyvinylidene fluoride (a very important fluoropolymer) and copolymers, in which iodofluoroalkanes are often used as chain transfer agents and polyvinylidene fluoride products (oligomers) with an iodo end are generated. , The cascade PIE strategy and data-screening algorithm can be expanded to nontarget identification for other pollutants besides IPFAAs, provided that they can generate diagnostic fragment ions in DDA mode. The nontarget identification and comprehensive characterization outcomes present new insights into the occurrence of IPFAAs in the water environment.…”
Section: Resultsmentioning
confidence: 99%
“…Despite increasing research attention on iodinated PFASs, almost all previously reported iodinated PFASs were nonionizable or neutral compounds, such as PFIs and FTIs. In contrast, ionizable iodinated PFASs, including iodine-containing polyfluoroalkyl carboxylic acids (IPFCAs) and iodine-containing polyfluoroalkyl sulfonic acids (IPFSAs), are still rarely reported. , In a recent study on nontarget screening and analysis of PFASs, we unexpectedly discovered some iodine-containing polyfluoroalkyl acids (IPFAAs), including both IPFCAs and IPFSAs, in fluorochemical industry wastewater with relatively high concentrations. , However, the previous nontarget analysis method was unable to detect IPFAAs in samples as complete as possible, and some IPFAAs might be missed, particularly low-abundance species. Therefore, more sophisticated analytical approaches, such as PIE and cascade PIEs, are needed for the comprehensive characterization of IPFAAs in environmental matrices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By virtue of the recently developed cutting-edge chromatographic and mass spectrometric techniques, nontarget analysis methods have been rapidly developed and applied to screening and identification of environmental pollutants, e.g., identification of HOPs in environmental matrices . In environmental studies concerning nontarget analysis, the applied chromatographic and mass spectrometric techniques mainly involve gas chromatography–quadrupole–time-of-flight mass spectrometry, liquid chromatography–quadrupole–time-of-flight mass spectrometry, gas chromatography–quadrupole–Orbitrap–high-resolution mass spectrometry (GC-Q-Orbitrap-HRMS), and liquid chromatography–quadrupole–Orbitrap–high-resolution mass spectrometry (LC-Q-Orbitrap-HRMS) . By means of these GC/LC-HRMS techniques, numerous halogenated organic compounds have been screened and identified, e.g., halogenated polycyclic aromatic hydrocarbons (H-PAHs), halogenated disinfection byproducts, and mix-chlorinated/brominated organic compounds (OClBrs) .…”
Section: Introductionmentioning
confidence: 99%
“…32 In environmental studies concerning nontarget analysis, the applied chromatographic and mass spectrometric techniques mainly involve gas chromatography−quadrupole− time-of-flight mass spectrometry, 33 liquid chromatography− quadrupole−time-of-flight mass spectrometry, 34 gas chromatography−quadrupole−Orbitrap−high-resolution mass spectrometry (GC-Q-Orbitrap-HRMS), 35 and liquid chromatography−quadrupole−Orbitrap−high-resolution mass spectrometry (LC-Q-Orbitrap-HRMS). 36 By means of these GC/LC-HRMS techniques, numerous halogenated organic compounds have been screened and identified, e.g., halogenated polycyclic aromatic hydrocarbons (H-PAHs), 37 halogenated disinfection byproducts, 34 and mix-chlorinated/brominated organic compounds (OClBrs). 32 Furthermore, some pioneer studies have reported the comprehensive characterization of HOPs in environmental media.…”
Section: ■ Introductionmentioning
confidence: 99%